Assimilation as 'false consciousness': Higher education immigrant students' acculturation beliefs and experiences. (July 2021) - Lewis, Lyn
Abstract: Immigrant students hold conflicting perspectives regarding their acculturation into higher education contexts in that they tend to favour integration (recognition of minority ethnic cultures) whilst expecting assimilation (adoption of dominant culture); the former expressed in principle and preference, while the latter is revealed through expectation and experience. The concept of assimilation as 'false consciousness' is presented to explain this contrast in acculturation preference and experience. This article reports on an empirical study of eight higher education immigrant students at a New Zealand university. A qualitative methodology used a questionnaire and interviews to explore participants' understandings and experiences of four concepts: adaptation orientations, behaviour shifts, assimilation as false consciousness, and invisibility in the learning environment. Findings indicate the contradictions between preferences and behaviours as a false consciousness, which leads to an unexamined and uncritical acceptance of assimilation, which in turn reflects in the invisibility of immigrant students in the learning environment. An argument is made for refinement of the 'integration' orientation of Berry's (1997) acculturation and adaptation model. First, to locate education contexts as bicultural within the 'public domain' rather than assimilationist; and second, to incorporate subcategories to reflect nuanced positioning within the orientation. This is based on the belief that to break the legacy of assimilation as false consciousness, higher education contexts should intentionally offer critical multicultural and intercultural education learning experiences to support the integration of acculturating immigrant students.